Cost-Benefit Analysis of the Fattening of Morkaraman Lambs with Different Dietary Plant Protein Sources - Mazhar Burak Can; Alperen Varalan; Halit İmik (Turkish Journal of Agriculture: Food Science and Technology)
This study investigated the effects of different plant protein sources incorporated into feed concentrates on the live weight gain and feed conversion ratio of Morkaraman lambs by days 28, 42 and 56 of fattening, and presents a cost-benefit analysis. The study animals included 24 male Morkaraman lambs with a mean age of 9 months, which were assigned to 3 study groups. The dietary plant protein sources provided to the animals were soybean meal and safflower meal in Group I, wheat gluten in Group II, and corn gluten in Group III. The total feed intake values (kg) of Group I, Group II and Group III were 40.75±1.08, 39.18±0.88, and 37.67±0.62, respectively, during the period between days 0-28 of fattening; 62.77±1.67, 60.14±0.96, and 57.54±1.28, respectively, during the period between days 0-42 of fattening; and 83.31±1.89, 77.79±1.43, and 75.97±1.67, respectively, during the period between days 0-56 of fattening (p<0.05). The live weight gain values (kg) of Group I, Group II and Group III during the period between days 0-56 of fattening were 14.82±0.84, 11.97±0.51, and 13.71±0.91, respectively (p<0.05). The feed conversion ratio was observed not to have a statistically significant effect on production yields (p>0.05). In conclusion, while the highest income from live weight gain during the period between days 0-56 of fattening was achieved with the use of soybean meal and safflower meal as dietary plant protein sources, the lowest fattening cost was achieved with the use of corn gluten.